MRI of the Elbow – Update 2024 - Schinnerl, Christoph; Weber, Marc-André; Benninger, Emanuel; Fischer, Tim S.; Falkowski, Anna L. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Elbow pain can result in significant morbidity. MRI can help diagnosing the cause of elbow pain.Based on a systematic literature search as well as knowledge gained through frequent participation in conferences dedicated to advances in musculoskeletal imaging, this review aims to give a brief overview of normal anatomy and common pathologies of tendons and ligaments of the elbow on magnetic resonance imaging.Stabilization of the elbow joint is provided by osseous structures and passive ligamentous and active muscular support. Loss of these important stabilizers, due to trauma and overuse, can result in elbow instability. Additional MR views or intra-articular contrast media can be useful for the detection of specific pathologies.MRI is frequently used to detect posttraumatic or chronic conditions, which can lead to posterolateral or posteromedial elbow instability. Knowledge of normal anatomy, variants, pathologies, as well as appropriate imaging is crucial to make the diagnosis.
Keywords: elbow; MR-imaging; posterolateral rotatory instability; posteromedial rotatory instability; symptomatic minor instability of the lateral elbow (SMILE)